Solid waste-based thermal insulation material and preparation method thereof
By preparing a solid waste-based thermal insulation material containing amino-modified waste rubber porous particles, the problem of building materials in the prior art being unable to balance strength and thermal insulation performance has been solved, and the preparation of building materials with high strength and excellent thermal insulation performance has been achieved.
Patent Information
- Application Number
- CN202511555340.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-29
- Publication Date
- 2026-01-09
- Estimated Expiration
- 2045-10-29
AI Technical Summary
Existing building materials, when utilizing solid waste, cannot simultaneously achieve high mechanical strength and excellent thermal insulation performance.
Solid waste-based thermal insulation materials are prepared by using raw materials such as cement, desulfurized gypsum, fly ash, aggregates, and amino-modified waste rubber porous particles through a specific preparation method. The porous structure and modified hydrophilicity of the amino-modified waste rubber porous particles are combined with a foaming agent to form a uniform slurry and mold it, thus producing a material with high strength and excellent thermal insulation performance.
This technology enables the resource utilization of solid waste and produces building materials with high mechanical strength and excellent thermal insulation performance, solving the problem that existing technologies struggle to balance mechanical strength and thermal insulation performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials, specifically to a solid waste-based thermal insulation material and its preparation method. Background Technology
[0002] Currently, the comprehensive utilization rate of solid waste is low, and its stockpiling and disposal occupy a large amount of land, causing serious pollution to land and water resources. Although there are some studies on using solid waste such as desulfurized gypsum, steel slag, and waste rubber granules to make building materials, the mechanical strength and thermal insulation performance of the prepared building materials are often not ideal, making it difficult to achieve both. Summary of the Invention
[0003] Purpose of the invention: To address the above-mentioned technical problems, this invention proposes a solid waste-based thermal insulation material and its preparation method.
[0004] The technical solution adopted is as follows: A solid waste-based thermal insulation material is made from the following raw materials in parts by weight: 60-70 parts cement, 10-20 parts desulfurized gypsum, 5-10 parts fly ash, 5-10 parts aggregate, 10-20 parts amino-modified waste rubber porous particles, 0.1-0.5 parts water-reducing agent, 0.5-1 part foaming agent, and 40-60 parts water.
[0005] Furthermore, the preparation method of the amino-modified waste rubber porous particles is as follows: S1: Use organic solvents to swell the waste rubber powder obtained from coarse crushing; S2: Subsequently activated under ultrasonic treatment; S3: Use liquid nitrogen to cool it and then pulverize it at low temperature to obtain porous waste rubber particles; S4: Finally, graft the porous waste rubber particles with organic amine.
[0006] Furthermore, the organic solvent in S1 is an alkane solvent and / or an aromatic hydrocarbon solvent.
[0007] The alkane solvent is n-hexane, cyclohexane, n-heptane, etc., and the aromatic hydrocarbon solvent is benzene, toluene, or xylene.
[0008] The preferred organic solvent is toluene.
[0009] Furthermore, the activation temperature in S2 is 40-60℃.
[0010] Furthermore, the low-temperature pulverization temperature in S3 is ≤-5℃.
[0011] Furthermore, S4 is detailed as follows: Porous waste rubber particles are added to an acidic potassium permanganate solution, heated and stirred to react, then filtered out and washed until neutral to obtain carboxylated porous waste rubber particles. The carboxylated porous waste rubber particles are then subjected to an amidation reaction with an organic amine.
[0012] Furthermore, during the amidation reaction, the carboxylated porous waste rubber particles are first acylated and then amidated with an organic amine.
[0013] Furthermore, the organic amine is a diamine or a triamine.
[0014] The diamine is a compound with 10 or fewer carbon atoms and containing two amino groups, and the triamine is a compound with 10 or fewer carbon atoms and containing three amino groups.
[0015] The organic amine is preferably ethylenediamine.
[0016] Furthermore, the foaming agent is composed of aluminum trichloride and sodium bicarbonate.
[0017] Furthermore, the mass ratio of aluminum trichloride to sodium bicarbonate is 1-4:1-4.
[0018] Bicarbonate ions and aluminum ions can undergo a double hydrolysis reaction under aqueous conditions to produce carbon dioxide gas, which can achieve the purpose of foaming cement paste. The reaction equation is as follows: Al 3+ +3HCO3 - →Al(OH)3 + 3CO2 This invention provides a method for preparing a solid waste-based thermal insulation material, characterized in that cement, desulfurized gypsum, fly ash, aggregate, amino-modified porous waste rubber particles, and water-reducing agent are added to water and stirred until a uniform slurry is formed. A foaming agent is then added to the slurry and stirred rapidly to disperse the foaming agent evenly, resulting in a foamed slurry. The foamed slurry is then molded, demolded, and cured.
[0019] The beneficial effects of this invention are: This invention provides a solid waste-based thermal insulation material. Desulfurized gypsum is a byproduct of flue gas desulfurization in coal-fired power plants. Replacing part of the cement can reduce cement consumption, which is in line with the goals of circular economy and environmental protection. The sulfate particles of desulfurized gypsum can better stimulate the pozzolanic activity of fly ash, which is conducive to the formation of ettringite crystals and CSH gel. The hydration products produced can fill the pores and improve the mechanical strength of the thermal insulation material.
[0020] In recent decades, with the rapid development of the automotive industry, how to handle waste car tires has become an important research topic. Although directly adding crushed waste tires as rubber particles has an adverse effect on the strength of concrete materials, it can enhance the thermal insulation performance, toughness, ductility, energy dissipation, damping ratio, and impact resistance of concrete materials. In this invention, the porous structure of amino-modified waste rubber porous particles can reduce the thermal conductivity of insulation materials. Moreover, after amino modification, the hydrophilicity of waste rubber porous particles is enhanced, resulting in better slurry dispersion during preparation and effectively preventing agglomeration. Furthermore, the grafted amino groups in the porous structure can selectively adsorb and retain CO2, thus having a certain slow-release effect. This effectively avoids the large amount of CO2 foam generated instantaneously by the foaming agent, which causes abnormally large pores inside the insulation material, leading to a decrease in thermal insulation performance and mechanical strength.
[0021] This invention utilizes solid waste to produce building insulation materials, which not only turns waste into treasure, but also produces solid waste-based insulation materials with high mechanical strength and excellent insulation performance. Detailed Implementation
[0022] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0023] Cement: PO42.5, ordinary Portland cement, Conch Cement; Desulfurized gypsum: Produced by Henan Qiangnai New Building Materials Co., Ltd., its main component is hemihydrate gypsum; Fly ash: Grade II, Yatai Group Shenyang Building Materials Co., Ltd.; Aggregate: Particle size 1-3mm, bulk density 1221.2kg / m³ 3 River sand; Amino-modified porous waste rubber granules: self-made; Polycarboxylate superplasticizer: water reduction rate 45%, Nanjing Xinyi Synthetic Technology Co., Ltd.; Aluminum trichloride: analytical grade, Langfang Qianyao Technology Co., Ltd.; Sodium bicarbonate: analytical grade, Aladdin; Water: tap water.
[0024] Example 1: A solid waste-based thermal insulation material is made from the following raw materials in parts by weight: 65 parts cement, 15 parts desulfurized gypsum, 10 parts fly ash, 8 parts aggregate, 15 parts amino-modified waste rubber porous particles, 0.3 parts polycarboxylate superplasticizer, 0.4 parts aluminum trichloride, 0.4 parts sodium bicarbonate, and 50 parts water.
[0025] The preparation method of amino-modified waste rubber porous particles is as follows: Waste rubber powder is made from discarded rubber tires through cutting, steel wire separation, and coarse crushing, with a bulk density of 290.1 kg / m³. 3 The particle size is 40-60 mesh. Take 100g of waste rubber powder and add it to 500ml of toluene. Swell for 12h at room temperature and pressure. Then heat to 50℃ and ultrasonically activate for 8h. Filter out the waste rubber powder, cool it rapidly with liquid nitrogen for 10s, and dry it in an oven at 60℃ for 10h. Take it out and crush it into 400 mesh porous waste rubber particles with a low temperature pulverizer at -8℃. Prepare a 1000ml 5wt% aqueous solution of potassium permanganate. Add an appropriate amount of sulfuric acid to adjust the pH of the system to 3 to obtain an acidic potassium permanganate solution. Add porous waste rubber particles and stir at 35℃ for 5 hours. Filter out the solid and wash it repeatedly with oxalic acid solution and distilled water until no potassium permanganate purple color remains. Dry it in an oven at 60℃ for 10 hours and then add it to 500ml of dichloromethane. Add 15ml of thionyl chloride and heat to reflux for 5 hours. After the reaction is complete, remove the dichloromethane and the remaining thionyl chloride by vacuum distillation. Add the obtained product to 500ml of ethylenediamine and heat to reflux for 10 hours. After the reaction is complete, filter out the product, wash it with water until neutral, and finally dry it in an oven at 60℃ for 10 hours.
[0026] The preparation method of the above-mentioned solid waste-based thermal insulation material: Cement, desulfurized gypsum, fly ash, aggregate, amino-modified waste rubber porous particles, and polycarboxylate superplasticizer are added to water and stirred until a uniform slurry is formed. Aluminum trichloride and sodium bicarbonate are added to the slurry and stirred rapidly at 300 r / min to disperse the foaming agent evenly, resulting in a foamed slurry. The foamed slurry is poured into a mold and cured at room temperature for 24 hours before demolding to obtain a test block. The test block is then placed in a standard curing chamber at a temperature of (20±2)℃ and a relative humidity of 95% for continued curing until it reaches an age of 28 days.
[0027] Example 2: A solid waste-based thermal insulation material is made from the following raw materials in parts by weight: 70 parts cement, 10 parts desulfurized gypsum, 10 parts fly ash, 5 parts aggregate, 20 parts amino-modified waste rubber porous particles, 0.1 parts polycarboxylate superplasticizer, 0.4 parts aluminum trichloride, 0.4 parts sodium bicarbonate, and 60 parts water.
[0028] The preparation method of amino-modified waste rubber porous particles is the same as in Example 1.
[0029] The preparation method of the above-mentioned solid waste-based thermal insulation material: Cement, desulfurized gypsum, fly ash, aggregate, amino-modified waste rubber porous particles, and polycarboxylate superplasticizer are added to water and stirred until a uniform slurry is formed. Aluminum trichloride and sodium bicarbonate are added to the slurry and stirred rapidly at 300 r / min to disperse the foaming agent evenly, resulting in a foamed slurry. The foamed slurry is poured into a mold and cured at room temperature for 24 hours before demolding to obtain a test block. The test block is then placed in a standard curing chamber at a temperature of (20±2)℃ and a relative humidity of 95% for continued curing until it reaches an age of 28 days.
[0030] Example 3: A solid waste-based thermal insulation material is made from the following raw materials in parts by weight: 60 parts cement, 20 parts desulfurized gypsum, 5 parts fly ash, 10 parts aggregate, 10 parts amino-modified waste rubber porous particles, 0.5 parts polycarboxylate superplasticizer, 0.25 parts aluminum trichloride, 0.25 parts sodium bicarbonate, and 40 parts water.
[0031] The preparation method of amino-modified waste rubber porous particles is the same as in Example 1.
[0032] The preparation method of the above-mentioned solid waste-based thermal insulation material: Cement, desulfurized gypsum, fly ash, aggregate, amino-modified waste rubber porous particles, and polycarboxylate superplasticizer are added to water and stirred until a uniform slurry is formed. Aluminum trichloride and sodium bicarbonate are added to the slurry and stirred rapidly at 300 r / min to disperse the foaming agent evenly, resulting in a foamed slurry. The foamed slurry is poured into a mold and cured at room temperature for 24 hours before demolding to obtain a test block. The test block is then placed in a standard curing chamber at a temperature of (20±2)℃ and a relative humidity of 95% for continued curing until it reaches an age of 28 days.
[0033] Example 4: A solid waste-based thermal insulation material is made from the following raw materials in parts by weight: 70 parts cement, 20 parts desulfurized gypsum, 10 parts fly ash, 10 parts aggregate, 20 parts amino-modified waste rubber porous particles, 0.5 parts polycarboxylate superplasticizer, 0.5 parts aluminum trichloride, 0.5 parts sodium bicarbonate, and 60 parts water.
[0034] The preparation method of amino-modified waste rubber porous particles is the same as in Example 1.
[0035] The preparation method of the above-mentioned solid waste-based thermal insulation material: Cement, desulfurized gypsum, fly ash, aggregate, amino-modified waste rubber porous particles, and polycarboxylate superplasticizer are added to water and stirred until a uniform slurry is formed. Aluminum trichloride and sodium bicarbonate are added to the slurry and stirred rapidly at 300 r / min to disperse the foaming agent evenly, resulting in a foamed slurry. The foamed slurry is poured into a mold and cured at room temperature for 24 hours before demolding to obtain a test block. The test block is then placed in a standard curing chamber at a temperature of (20±2)℃ and a relative humidity of 95% for continued curing until it reaches an age of 28 days.
[0036] Comparative Example 1: It is basically the same as Example 1, except that waste rubber powder is added directly.
[0037] Comparative Example 2: This is basically the same as Example 1, except that porous waste rubber particles are used instead of amino-modified porous waste rubber particles.
[0038] The preparation method of amino-modified porous waste rubber particles is as follows: Waste rubber powder is made from discarded rubber tires through cutting, steel wire separation, and crushing, with a bulk density of 290.1 kg / m³. 3 The particle size is 40-60 mesh. Take 100g of waste rubber powder and add it to 500ml of toluene. Swell for 12h at room temperature and pressure. Then heat to 50℃ and ultrasonically activate for 8h. Filter out the waste rubber powder, cool it rapidly with liquid nitrogen for 10s, and dry it in an oven at 60℃ for 10h. Take it out and crush it into 400 mesh porous waste rubber particles with a low temperature pulverizer at -8℃.
[0039] Comparative Example 3: It is basically the same as Example 1, except that carboxyl-modified porous waste rubber particles are used instead of amino-modified porous waste rubber particles.
[0040] The preparation method of carboxyl-modified porous waste rubber particles is as follows: Waste rubber powder is made from discarded rubber tires through cutting, steel wire separation, and crushing, with a bulk density of 290.1 kg / m³. 3The waste rubber powder, with a particle size of 40-60 mesh, was added to 500 ml of toluene and swelled at room temperature and pressure for 12 hours. It was then heated to 50°C and ultrasonically activated for 8 hours. The waste rubber powder was filtered out, rapidly cooled with liquid nitrogen for 10 seconds, and dried in a 60°C oven for 10 hours. It was then removed and pulverized into 400-mesh porous waste rubber particles using a low-temperature pulverizer at -8°C. A 5wt% potassium permanganate aqueous solution was prepared in 1000 ml, and an appropriate amount of sulfuric acid was added to adjust the pH to 3 to obtain an acidic potassium permanganate solution. The porous waste rubber particles were added and stirred at 35°C for 4 hours. The solid was filtered out and repeatedly washed with oxalic acid solution and distilled water until the potassium permanganate purple color disappeared. It was then dried in a 60°C oven for 10 hours.
[0041] Performance testing: The solid waste-based thermal insulation materials in Examples 1-4 and Comparative Examples 1-3 of this invention were made into corresponding test specimens for performance testing.
[0042] The compressive strength of the specimens was tested according to "JG / T266-2011 Foamed Concrete". The compressive strength was tested using a YAW-3000B pressure testing machine produced by Zhejiang Julong Company. The specimen size was 100mm×100mm×100mm, and the loading rate was 2000N / s. The thermal conductivity was tested according to GB / T32064-2015 "Temperature and thermal diffusivity of building materials - transient planar heat source test method", using a Hot Disk TPS 2500s thermal conductivity tester with a power of 45mW and a heating time of 20s. The pore structure was first photographed using a stereomicroscope to examine the cross-section of the pore structure in the foamed concrete, and then statistical analysis was performed on the pore structure using Image-Pro plus 6.0 (IPP) image software.
[0043] The test results are shown in Table 1 below: Table 1: As shown in Table 1 above, the solid waste-based thermal insulation material provided by this invention has high mechanical strength and excellent thermal insulation performance.
[0044] Furthermore, a comparison between Example 1 and Comparative Examples 1-3 shows that, since the rubber particles in Comparative Examples 1-3 were not modified with amino groups, the average pore size was abnormally large, resulting in a decrease in mechanical strength and thermal insulation performance.
[0045] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid waste-based thermal insulation material, characterized in that, Made from the following parts by weight of raw materials: 60-70 parts cement, 10-20 parts desulfurized gypsum, 5-10 parts fly ash, 5-10 parts aggregate, 10-20 parts amino-modified waste rubber porous particles, 0.1-0.5 parts water-reducing agent, 0.5-1 part foaming agent, and 40-60 parts water.
2. The solid waste-based thermal insulation material as described in claim 1, characterized in that, The preparation method of the amino-modified waste rubber porous particles is as follows: S1: Use organic solvents to swell the waste rubber powder obtained from coarse crushing; S2: Subsequently activated under ultrasonic treatment; S3: Use liquid nitrogen to cool it and then pulverize it at low temperature to obtain porous waste rubber particles; S4: Finally, graft the porous waste rubber particles with organic amine.
3. The solid waste-based thermal insulation material as described in claim 2, characterized in that, The organic solvent in S1 is an alkane solvent and / or an aromatic hydrocarbon solvent.
4. The solid waste-based thermal insulation material as described in claim 2, characterized in that, The activation temperature in S2 is 40-60℃.
5. The solid waste-based thermal insulation material as described in claim 2, characterized in that, S3 low-temperature grinding temperature ≤ -5℃.
6. The solid waste-based thermal insulation material as described in claim 2, characterized in that, S4 is as follows: Porous waste rubber particles are added to an acidic potassium permanganate solution, heated and stirred to react, then filtered out and washed until neutral to obtain carboxylated porous waste rubber particles. The carboxylated porous waste rubber particles are then subjected to an amidation reaction with an organic amine.
7. The solid waste-based thermal insulation material as described in claim 6, characterized in that, The organic amine is a diamine or a triamine.
8. The solid waste-based thermal insulation material as described in claim 1, characterized in that, The foaming agent is composed of aluminum trichloride and sodium bicarbonate.
9. The solid waste-based thermal insulation material as described in claim 8, characterized in that, The mass ratio of aluminum trichloride to sodium bicarbonate is 1-4:1-4.
10. A method for preparing a solid waste-based thermal insulation material as described in any one of claims 1-9, characterized in that, Mix cement, desulfurized gypsum, fly ash, aggregate, amino-modified porous waste rubber particles, and water-reducing agent with water until a uniform slurry is formed. Add foaming agent to the slurry and stir quickly to disperse the foaming agent evenly, thus obtaining a foamed slurry. The foamed slurry is then cast into molds, demolded, and cured.
Citation Information
Patent Citations
Heat-insulating and sound-isolating light foamed concrete material and preparation method thereof
CN103864382A
Method for preparing porous-structure tire rubber powder by wet crushing
CN111730786A
High-strength low-elasticity hydraulic abrasion-resistant concrete and preparation method thereof
CN114163207A
Sulfate-erosion-resistant concrete and preparation method thereof
CN114262181A
Novel smokeless soluble rubber powder composite modified asphalt and preparation method thereof
CN118085595A